EVALUASI SISTEM AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT DALAM PENGENDALIAN DAN PENILAIAN PRESTASI MANAJEMEN - Pratama, Ribut Satria (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to appraise and to analyze how the use of responsibility accountingsystem can have a role in appraising management performance. The research method is usingqualitative method since the researcher is not examining a hypothesis but to disclose an assumption byanalyzing, appraising and giving conclusion as a temporary answer of the ongoing problems. Theresearcher is using descriptive analysis technique since the researcher describes the research object justexactly what it is. It is found from the result of research that in its implementation, the organizationstructure of Puskopal Armatim Surabaya has clearly shown their responsibility and authority inaccord with the organization hierarchy but has not made responsibility code center yet, budgetingsystem is done by using Bottom Up Budgeting method even though not entirely using this method, atcost account code and the arrangement of responsibility report, the controllable and uncontrollable costhave not been divided.Keywords: Responsibility Accounting, Performance Evaluation, and Controllable Cost / Â Uncontrollable Cost